1992
DOI: 10.1063/1.463349
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-low temperature kinetics of neutral–neutral reactions: The reaction CN+O2 down to 26 K

Abstract: Ultralow temperature kinetics of neutral-neutral reactions. The technique and results for the reactions CN+O2 down to 13 K and CN+NH3 down to 25 K

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(52 citation statements)
references
References 13 publications
0
47
0
1
Order By: Relevance
“…In terms of overall reaction rate, only quite recently has the kinetic behavior of this reaction been accurately determined over a wide temperature range, from 26 K to 4000 K (4)(5)(6)(7). It was found that the thermal rate constant was relatively large and exhibited a pronounced negative temperature dependence, i.e., the rate constant decreased with increasing temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of overall reaction rate, only quite recently has the kinetic behavior of this reaction been accurately determined over a wide temperature range, from 26 K to 4000 K (4)(5)(6)(7). It was found that the thermal rate constant was relatively large and exhibited a pronounced negative temperature dependence, i.e., the rate constant decreased with increasing temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Practical difficulties to produce and measure radical concentrations made experimentalists to focus mainly on reactions which involve stable molecules. The development of new methods to investigate ultra low temperature kinetics, as the CRESU technique, 21 revealed however that reactions between neutral species could govern the dynamics at low-temperature regimes, for instance, in interstellar clouds. Recent examples of the possibilities of such approaches have been reported for the N+OH reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Methods to experimentally extract information on these resonances are extremely limited. Thus far, low-energy collisions have only been studied in cryogenic cell environments (19 ), or in supersonic gas expansions that are specifically designed to maintain a thermal equilibrium at temperatures as low as 6 K (20 ). Recently, reports have appeared on the study of cold inelastic collisions between alkali atoms and dimers in an optically trapped gas (21,22 ).…”
mentioning
confidence: 99%